Morphological and molecular characterization of native isolates of Jew’s ear mushroom (Auricularia auricula-judae) in Southern Kerala and its suitability in different culture media: Jews ear mushroom from Kerala - Vyshnavi, A. S.; R, Pramod; Thara, Susha S. (Mushroom Research, 2024)
Auricularia auricula-judae (Jew’s ear mushroom), an edible and medicinal mushroom, is widely distributed in Kerala, but is not cultivated or used by the common people. Surveys were conducted in 3 different Agro Ecological Units of southern Kerala to explore the native isolates of Jew’s ear mushroom and to study their morphological, microscopic and phylogenetic characters. The suitability of different media for their in-vitro culture was also studied. Nucleotide-level sequencing of the isolates using LSU primers confirmed all the collections to be A. auricula. All the sequences were deposited in the NCBI gene bank and accession numbers of each culture were obtained. Cultural studies showed that carrot agar medium was the best suited medium for the mycelial growth of Jew’s ear mushroom.